2018
DOI: 10.3390/cli6040080
|View full text |Cite
|
Sign up to set email alerts
|

New Breeding Techniques for Greenhouse Gas (GHG) Mitigation: Plants May Express Nitrous Oxide Reductase

Abstract: Nitrous oxide (N2O) is a potent greenhouse gas (GHG). Although it comprises only 0.03% of total GHGs produced, N2O makes a marked contribution to global warming. Much of the N2O in the atmosphere issues from incomplete bacterial denitrification processes acting on high levels of nitrogen (N) in the soil due to fertilizer usage. Using less fertilizer is the obvious solution for denitrification mitigation, but there is a significant drawback (especially where not enough N is available for the crop via N depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…The nitrous oxide reductase (Nos) reaction of the denitrification pathway is unique in that it represents the only biological sink of N 2 O, a greenhouse gas and a stratospheric ozone-depleting agent. Strategies employing Nos for controlling emissions of N 2 O are currently being developed, including transformation of plants with the nosZ gene for the Nos apoprotein or inoculation with genetically modified N 2 O-cracking strains [ 36 ]. In P. denitrificans , the nosZ ( pden_4219 ) gene is upregulated at both the mRNA and the protein level in semiaerobically grown cells even in the absence of nitrogen electron acceptors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nitrous oxide reductase (Nos) reaction of the denitrification pathway is unique in that it represents the only biological sink of N 2 O, a greenhouse gas and a stratospheric ozone-depleting agent. Strategies employing Nos for controlling emissions of N 2 O are currently being developed, including transformation of plants with the nosZ gene for the Nos apoprotein or inoculation with genetically modified N 2 O-cracking strains [ 36 ]. In P. denitrificans , the nosZ ( pden_4219 ) gene is upregulated at both the mRNA and the protein level in semiaerobically grown cells even in the absence of nitrogen electron acceptors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These benefits will become invaluable in the face of climate change, as some are predicting that H. abietis herbivory of conifers will increase as the global temperature increases (Haynes et al 2014;Wainhouse et al 2014). The establishment of a reliable tissue culture system also positions Hoopsii as a target for transgenesis; Norway spruce has been successfully transformed via Agrobacterium tumefaciens-mediated infection (Wenck et al 1999), and in this vein Hoopsii and other conifers may become hosts for manipulation to improve insect resistance, or to possibly serve as mediators of atmospheric phytoremediation (Demone et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the chances of fully reducing nitrous oxide, Demone et al in 2018 showed that many studies have recently looked into the transfer of nitrous oxide reductase to plants; however, this genetic transfer has yet to be commercialized and there are still some research gaps that need to be addressed. 18 could be successful, but requires further research. 19 In addition, the article estimated the potential impact of nitrous oxide reductase maize and calculated that the potential removal of nitrous oxide from the soil would be 43 kg ha À1 yr À1 , which is significantly higher than the observed soil emissions of 11 kg ha À1 yr À1 from fertilized corn fields.…”
Section: Biotechnologymentioning
confidence: 99%
“…In order to increase the chances of fully reducing nitrous oxide, Demone et al in 2018 showed that many studies have recently looked into the transfer of nitrous oxide reductase to plants; however, this genetic transfer has yet to be commercialized and there are still some research gaps that need to be addressed 18 . Strand et al have updated this idea in 2022: the cytosolic expression of nitrous oxide reductase in plants has shown to be unsuccessful, but the article suggests that the introduction of the protein complex in the mitochondria could be successful, but requires further research 19 .…”
Section: Introductionmentioning
confidence: 99%